The Impact of Rice Import Tariff toward Paddi’s Farmer and Rice Consumers Welfare - Dwi Haryono; Hanung Ismono (Politeknik Negeri Lampung, 2011)
This study aims to analyze the impact of rice import tariff policy for rice supply and demand, as well as the welfare level of the rice farmers and consumers of rice in the domestic market. The data used in this research is secondary data which is the time series data in 1990-2006. Analysis performed using Econometrics model in the form of simultaneous equations. Rice import tariff policy has positive effects on rice crop area of Java, the rice crop area Non-Java, Java rice productivity, rice prices at the producer level, and the price of rice at the consumer level, but a negative effect on rice stocks, imports of rice, and rice consumption. Increased import tariffs would reduce welfare only economic actors, on the other hand elimination of import tariffs will improve the welfare of economic actors.Â Key words: import tariff, welfare